2018
DOI: 10.1186/s13104-018-3873-9
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic supplements containing Lactobacillus reuteri does not affect the levels of matrix metalloproteinases and interferons in oral wound healing

Abstract: ObjectiveThe use of beneficial bacteria may stimulate wound healing. We performed a randomized, placebo-controlled double-blind cross-over study comprising ten healthy volunteers. The aim was to investigate the impact of topical and systemic applications of probiotic lactobacilli (Lactobacillus reuteri) on the healing of standardized wounds (punch biopsies) in the oral mucosa. The expression of selected matrix metalloproteinases (MMP’S) and interferons (IFN’s) was analyzed with multiplex immunoassays in the wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 22 publications
(20 reference statements)
0
21
0
Order By: Relevance
“…In these studies, the mechanism of action was typically not explored, but topical probiotic treatment resulted in improved healing as demonstrated by increased granulation tissue deposition, improved collagen concentration, and stimulation of angiogenesis. [33][34][35][36][37][38][39][40][41][42] However, not all models demonstrated an improvement in topical wound healing with probiotics [33][34][35][36][37][38][39][40][41][42][43][44] (Tables 1 and 2).…”
Section: Wound Healing and Topical Probiotic: General Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In these studies, the mechanism of action was typically not explored, but topical probiotic treatment resulted in improved healing as demonstrated by increased granulation tissue deposition, improved collagen concentration, and stimulation of angiogenesis. [33][34][35][36][37][38][39][40][41][42] However, not all models demonstrated an improvement in topical wound healing with probiotics [33][34][35][36][37][38][39][40][41][42][43][44] (Tables 1 and 2).…”
Section: Wound Healing and Topical Probiotic: General Studiesmentioning
confidence: 99%
“…They were able to reduce the erythema and oedema associated with CO 2 laser therapy, reduce skin sensitivity in patients with reactive skin, and increase ceramide concentration and skin hydration. [82][83][84][85] However, not all studies investigating topical probiotics have demonstrated superiority compared with traditional interventions 43,44 (Table 2).…”
Section: Wound Healing and Topical Probiotic: Non-pathologicmentioning
confidence: 99%
“…Activities of MMPs are regulated by TIMPs (Dollery et al 1995;Nagase et al 2006). Twetman et al (2018) suggested that enrichments encompassing L. reuteri cannot influence the levels of MMP and interferons in oral wound healing. Our results of gelatin zymography and RT-qPCR revealed that the activity and expression of MMP9 significantly decreased by HK-SON, unprocessed CSF and >100 kDa fraction of L. reuteri PTCC 1655 in comparison with the related controls.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous human studies have investigated the role of topical probiotics in various skin conditions . Skin conditions that have been investigated include atopic dermatitis, seborrhoeic dermatitis, acne and reactive skin.…”
Section: Addressing the Skin Microflora To Combat Disease Statesmentioning
confidence: 99%